Dietary habits of polar bears in Foxe Basin, Canada: possible evidence of a trophic regime shift mediated by a new top predator. Issue 16 (28th July 2016) - Galicia, Melissa P.; Thiemann, Gregory W.; Dyck, Markus G.; Ferguson, Steven H.; Higdon, Jeff W.
Abstract: Polar bear ( Ursus maritimus ) subpopulations in several areas with seasonal sea ice regimes have shown declines in body condition, reproductive rates, or abundance as a result of declining sea ice habitat. In the Foxe Basin region of Nunavut, Canada, the size of the polar bear subpopulation has remained largely stable over the past 20 years, despite concurrent declines in sea ice habitat. We used fatty acid analysis to examine polar bear feeding habits in Foxe Basin and thus potentially identify ecological factors contributing to population stability. Adipose tissue samples were collected from 103 polar bears harvested during 2010–2012. Polar bear diet composition varied spatially within the region with ringed seal ( Pusa hispida ) comprising the primary prey in northern and southern Foxe Basin, whereas polar bears in Hudson Strait consumed equal proportions of ringed seal and harp seal ( Pagophilus groenlandicus ). Walrus ( Odobenus rosmarus ) consumption was highest in northern Foxe Basin, a trend driven by the ability of adult male bears to capture large‐bodied prey. Importantly, bowhead whale ( Balaena mysticetus ) contributed to polar bear diets in all areas and all age and sex classes. Bowhead carcasses resulting from killer whale ( Orcinus orca ) predation and subsistence harvest potentially provide an important supplementary food source for polar bears during the ice‐free period. Our results suggest that the increasing abundance of killer whales and bowhead whales in the region could be indirectly contributing to improved polar bear foraging success despite declining sea ice habitat. However, this indirect interaction between top predators may be temporary if continued sea ice declines eventually severely limit on‐ice feeding opportunities for polar bears. Abstract : We used fatty acid analysis to determine polar bear feeding habits in Foxe Basin and thus potentially identify ecological factors contributing to population stability. The spatial and seasonal variation in diet suggests polar bears are exploiting locally abundant prey and may seasonally shift their foraging preferences. In addition, the presence of bowhead whales in the diets of bears suggests that scavenging on carcasses provided by killer whale predation may serve as an increasingly important supplemental food source.